The activities at world data center for geomagnetism Mumbai, India - Doiphode, M.G.; Nimje, R.; Alex, S. (My University, 2013)
The World Data Centre for Geomagnetism, Mumbai has functioned as a division of the Indian Institute of Geomagnetism, Navi Mumbai since its full fledged activities commenced in 1991 in coordination with the International Council of Scientific Unions (ICSU) Panel on World Data Centres. Responsibility for the compilation of final hourly absolute values from nine of the Indian magnetic observatories and deposition of this data to the World Data Centres is undertaken at the centre. We have utilized the full advantage of technology advancement in upgrading our data preservation and conservation policy at various levels. In recent years, the centre has prioritized its activities related to digital preservation to ensure digital archiving of magnetic data from the traditional media and also digital conservation of very old hand written/printed data volumes and magnetograms. In view of the scientific importance of data from the Colaba-Alibag Magnetic Observatory, old magnetograms and data volumes are being converted to digital images for long term preservation. In the digital preservation process, the creation of metadata has become an important component in storing information related to old and current scientific records for future use. The centre also hosts a database driven website to make datasets available online to the global scientific community.
Keywords: Digital preservation; Colaba-Alibag magnetic observatory; Geomagnetic data archives; ICSU; World data centre